(untitled) (Fisioterapia e Pesquisa, 2011)
The photogrammetric analysis can be done by using different softwares. Thus, the purpose of this study was to assess the reliability and the usability of three different softwares during the hip flexion photogrammetric analysis and to discuss the qualitative and quantitative aspects of each one. Twenty-six volunteers participated in this study with age between 19 and 30 years old (x=25.4 years, SD=2.5) who underwent the sit-to-reach test through adapted Wells´ bench. Reflective skin markers were positioned in the anterior superior iliac spine and greater trochanter. The image acquisition was collected in the maximum limit of test execution. All softwares showed a high reliability between measures, besides it was presented specifics advantages and disadvantages during adoption one of them. SAPO´s software was considered with major points for professional practice, although taking the analysis for scientific research all softwares demonstrated characteristics that must be taken into consideration before adopting them.